1999
DOI: 10.1073/pnas.96.15.8438
|View full text |Cite
|
Sign up to set email alerts
|

Hot-spot mutants of p53 core domain evince characteristic local structural changes

Abstract: Most of the oncogenic mutations in the tumor suppressor p53 map to its DNA-binding (core) domain. It is thus a potential target in cancer therapy for rescue by drugs. To begin to understand how mutation inactivates p53 and hence to provide a structural basis for drug design, we have compared structures of wild-type and mutant p53 core domains in solution by NMR spectroscopy. Structural changes introduced by five hot-spot mutations (V143A, G245S, R248Q, R249S, and R273H) were monitored by chemical-shift changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
220
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(242 citation statements)
references
References 23 publications
21
220
1
Order By: Relevance
“…In contrast to other structural mutants, G245S did not interact with p63 or p73 (Figure 7). However, the p53-G245S protein is only locally distorted in comparison with p53-R175H and p53-R282W, which are distorted globally (Wong et al, 1999;Brosh and Rotter, 2009). These findings suggest that the extent of mutant p53 protein distortion may also dictate its ability to sequester p63 and p73.…”
Section: Input Igg Pab1620mentioning
confidence: 95%
“…In contrast to other structural mutants, G245S did not interact with p63 or p73 (Figure 7). However, the p53-G245S protein is only locally distorted in comparison with p53-R175H and p53-R282W, which are distorted globally (Wong et al, 1999;Brosh and Rotter, 2009). These findings suggest that the extent of mutant p53 protein distortion may also dictate its ability to sequester p63 and p73.…”
Section: Input Igg Pab1620mentioning
confidence: 95%
“…R175, G245, R249, R282) diminish binding by destabilizing the tertiary structure of p53 DBD. 27,28 Mutation at position 248 (R248), in addition to breaking DNA-protein contacts, also introduces extensive structural changes into the DBD. 27 Among these mutations are also those that lead to the loss or significant decrease in Zn 2 þ ions, normally chelated by C176 and H179 of the L2 loop and by C238 and C242 of the L3 loop.…”
Section: P53 Has Two Autonomous Dna-binding Domainsmentioning
confidence: 99%
“…Structural consequences of oncogenic mutations in the p53 DNA-binding domain The cocrystal structure of the wild-type p53 core domain bound to DNA together with more recent nuclear magnetic resonance (NMR) and X-ray studies on tumor-derived core domain mutants have revealed the structural impact of amino-acid residues that are most frequently mutated in human cancers (Cho et al, 1994;Wong et al, 1999;Joerger et al, 2004Joerger et al, , 2005aAng et al, 2006). The so-called DNA contact mutants, for example R273H and R248Q, carry substitutions of residues that directly contact DNA.…”
Section: Structural Basis For Mutant P53 Reactivationmentioning
confidence: 99%